ANALYSIS OF THE INFLUENCE OF CURRENT RATIO, DEBT TO EQUITY RATIO, NET PROFIT MARGIN AND TOTAL ASSETS TURNOVER ON STOCK PRICES IN REGISTERED PRIMARY CONSUMER GOODS SECTOR COMPANIES ON THE INDONESIAN STOCK EXCHANGE PERIOD 2018-2022 - Dedek Adelina Sidebang; Fuji Astuty; Meysa Adesty Br Sebayang; Boydo Simbolon; Anggono (Mount Hope Economic Global Journal, 2024)
The Consumer Non-Cyclicals sector is an industrial sector consisting of companies that produce products and services consumed primarily or are non-cyclical in nature. This sector plays an active role in supporting the Indonesian economy and influences the national economic growth. The Consumer Non-Cyclicals sector is expected to grow in line with population growth and increasing income levels. However, investors need to consider many factors before starting their investment activities in the capital market, one of which is the company's valuation. Therefore, it is important for investors to understand how a company's value is reflected in its stock price. Stock price is formed based on supply and demand in the stock market, which is influenced by the interaction of stock sellers and buyers driven by their expectations of company profits, in which case an investor holds ownership rights. There are various types of financial ratios that can be used for various purposes in analysis, but the financial ratios used in this study are liquidity ratio measured by current ratio, solvency ratio measured by debt to equity ratio, profitability ratio measured by net profit margin, and activity ratio measured by total asset turnover, with stock price as the dependent variable. The extent to which the current ratio, debt to equity ratio, net profit margin, and total asset turnover affect stock prices is the focus of this research. Purposive sampling method is used in this analysis to obtain data from 125 out of 20 Consumer Non-Cyclicals sector companies listed on the IDX for the years 2018-2022. Hypotheses are evaluated using a series of tests employing linear regression analysis. The findings of hypothesis testing for the period 2018-2022 reveal that the current ratio, debt to equity ratio, net profit margin, and total asset turnover ratios collectively (simultaneously) affect the stock prices of Consumer Non-Cyclicals sector companies listed on the IDX for the years 2018-2022. This means that the research model is worthy of continuation in subsequent analyses. Furthermore, partially throughout the period 2018-2022, the current ratio and debt to equity ratio in Consumer Non-Cyclicals sector companies listed on the IDX for the years 2018-2022 do not have a significant impact on stock prices, while net profit margin and total asset turnover ratios in Consumer Non-Cyclicals sector companies listed on the IDX for the years 2018-2022 have a significant impact on stock prices.